Analysis of firm size in moderating profitability and asset growth on capital structure (studies on manufacturing companies listed on the indonesian stock exchange) - Martin; Zakia Fadila; Zahri Fadli (Enrichment : Journal of Management, 2022)
In normal operations the company needs capital to be used as a basis for financing in carrying out the company's normal operations, the capital contained in the company is useful to move the company so that it can operate in achieving company goals, profits, and investment from external parties of the company can provide an increase in company capital plus loans made provided by third parties can improve the capital structure of the company. This research is a type of quantitative research that processes data into numbers or quantitative data. The object of this study, namely manufacturing companies in the food and beverage sector listed on the Indonesian stock exchange, which will be taken as research data are the financial reports of each company for the 2017-2021 period. Profitability has a significant effect on capital structure, asset growth has a significant effect on capital structure, Firme size can strengthen the effect of profitability on capital structure, and Firme size strengthens the effect of asset growth on capital structure